Development of an educational board game to introduce traditional snack culture to children in RA Kuttab Labib - Hapsari, Junda; Fitriana Bahri, Nurul (Gelar: Jurnal Seni Budaya, 2025)
The erosion of traditional snack culture, especially among children, underscores the need for innovative educational tools to foster cultural awareness. This study aims to design an educational board game concept to introduce traditional Indonesian snack culture to children aged 4–6, targeting their developmental stage where cognitive and social skills are rapidly forming, supported by Piaget's cognitive development theory. A preliminary study and data collection were conducted at RA Kuttab Labib Bandung through observation and interviews to determine children's needs in cultural learning and the types of educational toys that are preferred and considered adequate for children. Data analysis was conducted using thematic analysis by literature studies on culture, educational toys, child anthropometry, and ergonomics. The data produced is the initial capital to design a board game with a design thinking approach that can encourage researcher innovation, but it is still based on user needs. This study contributes to the development of culturally focused learning media by providing innovative and concrete toy designs that combine traditional culinary elements with the potential to be implemented in early childhood environments to support cultural preservation and education.